The Image of Woman in the Sintren and Kuda Kepang Arts: Gender Reality and Aesthetic Exploration - Lestari, Wahyu; Iryanti, Veronica Eny; Barus, Syukur Samuel (Harmonia: Journal of Arts Research and Education, 2021)
The image of women that is actualized through the construction of gender roles, positions, and adaptation processes in artistic expression through Sintren and Kuda Kepang performances is very different. In this regard, the research aims to: (1) explain the forms of art performances of Sintren and Kuda Kepang; and (2) explain the image of women in the art performances of Sintren and Kuda Kepang in the context of gender reality and aesthetic exploration. The research was conducted on the art of Sintren Ujung Gede in Pemalang Regency and Kuda Kepang Turonggoseto in Semarang Regency. The research data were collected using the techniques of (1) observation, (2) interviews, and (3) document studies. The validity of the research data was carried out using the confirmability technique. The study used an interactive model analysis procedure, which was carried out with the stages of data collection, data reduction, data classification, and drawing conclusions. The results show that: (1) Sintren and Kuda Kepang arts are forms of traditional folk-art performances in which there is a scene of trance. This art is usually performed on stage or open arena by involving women as players; (2) The presence of women in the Sintren performances is a requirement that traditionally must be fulfilled until now. On the other hand, in the Kuda Kepang performances, the presence of women is a new phenomenon that provides opportunities and freedom for women to express themselves through dance. In the Sintren performance, the position of women becomes the center, subject, and object during the performance process. As a result, changes in the function of arts often result in the exploitation of Sintren dancers. On the other hand, in the Kuda Kepang art, the involvement of women with all their adaptations provides a new space for resistance to the existing gender stereotypes.